Implications of Whatsapp Group-Based Health Education on the Behavior of Elderly Caregivers in Preventing Covid-19 Infection in Palembang City - Irwadi; Andre Utama Saputra (MultiTech Publisher, 2023)
Deployment Coronavirus Disease (COVID-19) increases the risk of infection in the elderly, especially elderly people who have the diseasecomorbid if infected it will worsen the condition of the elderly. Due to this pandemic. The aim of the research is to determine the inﬂuence of health-based education WhatsApp Group to knowledge, attitudes and actions caregiver elderly withcomorbid in preventing COVID-19 infection. Research design Quasi Eksperimen Pre Posttest With Non Equivalent Control Group. The total sample was 76 people consisting of 38 intervention groups and 38 control groups. Sampling method probability sampling by using techniques Sample Random Sampling. The research results showed that there was a signiﬁcant inﬂuence on the knowledge, attitudes and actions obtained (p < α = 0.05). Conclusion based health education WhatsApp Group eﬀectively improve knowledge, attitudes and actions caregiver elderly with comorbid in preventing COVID-19 infection.